Distant Love : personal life in the global age - Beck, Ulrich, 1944-; Beck-Gernsheim, Elisabeth, 1946-; Livingstone, Rodney (Malden, MA : Polity, 2014)
Love and family life in the global age: grandparents in Salonika and their grandson in London speak together every evening via Skype. A U.S. citizen and her Swiss husband fret over large telephone bills and high travel costs. A European couple can finally have a baby with the help of an Indian surrogate mother.
In their new book, Ulrich Beck and Elisabeth Beck-Gernsheim investigate all types of long-distance relationships, marriages and families that stretch across countries, continents and cultures. These long-distance relationships comprise so many different forms of what they call'world families', by which they mean love and intimate relationships between individuals living in, or coming from, different countries or continents. In all their various forms these world families share one feature in common: they are the focal point in which different aspects of the globalized world become embodied in the personal lives of individuals. Whether they like it or not, lovers and relatives in these families find themselves confronting the world in the inner space of their own lives. The conflicts between the developed and developing worlds come to the surface in world families - they acquire faces and names, creating confusion, surprise, anger, joy, pleasure and pain at the heart of everyday life. -- Provided by publisher.
Includes bibliographical references (pages [194]-207 and index.
Keywords: Communication in families; Long-distance relationships; Interpersonal relations; Globalization; Families; Families and relationships